2020
DOI: 10.3390/ijerph17072185
|View full text |Cite
|
Sign up to set email alerts
|

Validating Self-Reported Ad Recall as a Measure of Exposure to Digital Advertising: An Exploratory Analysis Using Ad Tracking Methodology

Abstract: Many mass media campaigns aimed at changing young people’s health behavior air on digital platforms rather than on broadcast media (e.g., television), given the intended audience’s preference for web-based communication. While research suggests self-reported ad recall correlates with exposure to television advertising, it remains unclear whether self-report measures are correlated with exposure to digital advertising. This study examined the association between an objective measure of digital ad exposure and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…These findings extend those from a recent study which found that self-reported ad recall had a dose-response relationship with the number of times an ad had been encountered during regular web browsing [8]. Results suggest that a dose-response relationship between actual message exposure and message recall persists, even within a digital experience.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings extend those from a recent study which found that self-reported ad recall had a dose-response relationship with the number of times an ad had been encountered during regular web browsing [8]. Results suggest that a dose-response relationship between actual message exposure and message recall persists, even within a digital experience.…”
Section: Discussionsupporting
confidence: 85%
“…Public Health 2020, 17, 8427 2 of 8 determine brand and ad awareness in both commercial marketing and the scientific study of mass communication [4,5]. Validity of these measures has been supported by population-level correlations between self-reported and objective, exogenous measures such as television TRPs [6,7], and, more recently, individual-level associations with digital impressions [8].…”
Section: Introductionmentioning
confidence: 99%
“… 16 Additionally, the more a respondent identified with the LGBT community, the more receptive they were to campaign advertisements. 19 To the extent that self-reported awareness is correlated with objective measures of exposure to digital advertising, 20 the campaign awareness and receptivity levels achieved by This Free Life are suggestive of early campaign implementation success. However, the minimum level of reach and receptivity required for an effective digital tobacco public education campaign remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are no objective methods for determining the proportion of a population exposed to a campaign's main video message/s across multiple channels, nor how many times each individual has been exposed. 34 Indeed, it is difficult to objectively measure a single person's frequency of exposure within the digital sphere, and the decline of third-party cookies (see online supplemental file for definitions of online media tracking and metrics) will make this even more difficult. 35 Given research showing objective measures of exposure via televised target audience rating points were typically strongly associated with self-reported campaign exposure, 36 37 one solution is to conduct studies to validate self-reported exposure to digital campaign messages against objective digital metrics (eg, impressions, video ads served and completed video views).…”
Section: Campaign Reachmentioning
confidence: 99%